Presidential elections of 1997: a comparative analysis of electoral provisions and stereotypes - Bielinis, Lauras (Politologija, 1998)
In this article, the author affirms that after the political process is settled and the politicians are able to present the society ideas that compete with each other, the electoral campaign is strengthened by a unilateral effect of broadcasting and circulation of the political presentations (political speaking). It must be emphasised that it is suitable for the candidate to speak at some distance. The reader, listener, or spectator watching TV, listening to the radio, or reading a newspaper is, on the one hand, forced to listen to the candidate through, but on the other hand, has no chance to join in the polemics.It must be stressed that during the Presidential elections of 1997, the society had been apt to transcend primitive mobilisational behavior. The author reminds us this primitive mobilisational behavior was formed by using the opposition between the "mine" and the "stranger's." In fact, the politicians were nevertheless trying to provoke and renovate this efficient value-classificative distribution to the furthest possible extent.Oftentimes, public speaking has a classificative character. Furthermore, public speaking turns understandable due to the usage of simple associations and stereotypes, so usual and routine for our conscience. Therefore, for the politician to speak in public means to mould between associations and stereotypes.On its turn, the stereotype has a characteristic of fixed regulations. Hence, with respect to this, we may mark out several levels:Personal level evaluations of the environment characteristic and important for that person alone.Evaluations with respect to interpersonal communication.Group-level evaluations, where the traces of a social stereotype may be found.Ideologies, which crystallise over a long time.Where the competition is not for the real values and decisions, but for stereotyped models of political activity, the society is brought into the action. Politics and elections become the arena where fights for personal social stereotypes occur.The events and their evaluations distract a person from reality; they become stereotypical models of political opinion based upon the conventionalised stereotypes.Save talking about political texts or a political discourse, many of us tend to confine themselves with few evaluations concerning the vagueness of the subject and the triviality of verificative opportunities. However, very often we simply forget that to speak, and speak in the public, is but to mould associations and stereotypes. That is why very often in the world of political evaluations, clear and correct functional relations between the cause and the outcome do not exist.Priorities of the politicians can be interpreted by using statistical methods, that is—studying the texts (political declarations, programmes and rules, interviews, etc.). However, always there is a huge likelihood of running a mistake. A word, for example, which was inscribed in the written text or was vocalised by the politician, may serve both as casual, that is—having particular meaning for the politician alone, and as a standard political category. Therefore, this is the place where risks and difficulty lie.Yet, in general, if we analyse the model as illustrating a tendency, the bias traced in accordance with public presentations of the politician, not as a static occurrence indicating to the limits (values and orientations) of the object we study, the aforementioned hurdles let the formation of the common model of the regulations and the actions of the politician involved.The author proceeds to elaborating upon the political text. He emphasises that the political text consists of a collection of political stereotypes, which defines the model regarding a specific political orientation of the politician concerned. Stereotypes, which conform to common political orientation and the expectations of the society, become the most important (compositional) words, on the one hand, delineating the value orientations of the text and, on the other, moulding the value trends in the structure of the text itself.It should be notified, that as soon as the text consumer has completed the reading and has come to understand the values inscribed there, this text consumer reduces, tightens it to the compositional meanings. The reader recalls the scale of values, orientations, and his own emotional condition at the time he read the text. In short summary, it can be stated that such an attitude towards the political text and the attempt to research it can be titled as systemotechnical, which means planning of the text under research, project making, and construction of it under the determined parameters.For those who research the place of value orientations and stereotypes in the system of a candidate's electoral rhetoric and declared worldly outlook, the content of the electoral programmes, texts of the candidates presented during the electoral campaign of the President of the Republic of Lithuania, 1997, is an exclusively interesting material.In this research, the author analyses the officially published programmes. In spite of the fact that it might be naive to expect final and exhaustive reflection of a candidate's activity and his political life via the programmes published, in fact, the electoral programme becomes the basic document that reveals the political, ideological, and organisational standpoint of a presidential candidate.There are different diapasons of the text analysis available. First of all, this regards the calculation of the parameters of the linguistic level, namely—phonetic, phonologic, prosodic, syntactic, semantic, or pragmatic parameters. In this case, democracy was picked as a dimension of the research. This may seem obvious that in Lithuania's political society democratic values have occupied an important place. In the career activity of a politician, an aptitude to manipulate with the complexes of democratic values becomes a compulsory "collection of a gentleman." It goes without saying that it becomes compulsory furthermore, because each candidate explicates his own criteria and understanding of democratic values, derives his own understanding of what their importance to political activity is.However, save knowing the political and ideological orientation of the candidate, then, save comparing his public declarations with the priorities he marks out in the text, we can trace down tendencies which, on their side, confirm or deny positions of the candidate with respect to the values and aspirations he has declared prima facie. The text of the programme displays the aims concerning the activities of the candidate, unspoken, and sometimes misunderstood, provisions in his own political activity. In addition, the text of the programme reflects the level of autonomy of the politician and his team, their place and niche in the communal political system, their dependence on subjective and objective factors affecting it.Despite the limitations of the research, the results provide an opportunity to understand the following: whether the politician contains an adequate understanding of the goals of the democratic, whether his programme conforms to the ideology he declares.The goal of establishing a hierarchy of priorities becomes a kind of an indicator concerning the declared value orientations of the leader and his team. On its turn, it gives us a chance to have a look at the established priorities pertaining to political standpoints, stereotypes, and political demands these politicians have.Provided the research of the programme's provisions, it turns out possible to make a conclusion that: first of all, the candidates to the post of the President of the Republic of Lithuania emphasise the orientations to the state. That can be explained as a vitality of the self-dependence of Lithuania during the entire XXth century. The majority of the candidates (with an exception of V. Landsbergis and R. Smetona) underline the necessity of a legal state. The two candidates, who highlighted the Nation and the Man, value the legal attributes of democracy insufficiently.
Keywords: -